The impact of pidgin english on beninese intermediate EFL learners’ communicative skills. the case study of Nigeria neighboring region secondary schools in the Benin republic - TEBA, Sourou Corneille (My University, 2022)
This paper examines the impact of Nigerian pidgin English (NPE) on intermediate EFL learners in Beninese secondary schools. The Objective is to take advantage of pidgin English to promote oral communication. A mixed-method research design has been used. The instrument includes questionnaires addressed to ten (10) EFL teachers and forty (40) randomly selected learners and classroom observations. The results showed that the NPE) has a positive impact on EFL learners’ communicative skills. This study suggested that the EFL process adapts to the context and draws the benefit from social and cultural content that induce motivation and participation to improve learners’ performance.
Keywords: intermediate EFL learners; pidgin english; communicative skills